YOUTH LANGUAGE UNCOVERED: META-SYNTHETIC INSIGHTS INTO GEN Z AND GEN ALPHA SLANG - Paoleti, Veronika Deyanova; Mujahidah, Nur Fathiyya Zahira (English Review: Journal of English Education, 2025)
This study aims to analyze the linguistic behaviors of Gen Z and Gen Alpha, focusing on their use of slang, the influence of digital platforms, and the broader cultural and societal implications of their language practices. A meta-synthetic research design was employed, synthesizing data from 30 academic articles, conference proceedings, and credible publications spanning 2016–2024. Thematic synthesis techniques were applied, including coding, categorization into thematic areas, and meta-synthesis to identify patterns and trends. Quantitative metrics, such as the frequency of slang usage on platforms like TikTok and Instagram, were also analyzed to examine inter-generational differences. The findings reveal that both generations use slang as a cultural marker, with Gen Z favoring socio-political expressions such as "no cap" and "woke," while Gen Alpha leans towards playful, meme-based phrases like "Skibidi" and "pog." Digital platforms significantly shape their linguistic behaviors, with TikTok fostering short-lived trends and Instagram blending slang with visual storytelling. Gen Z exhibits adaptability in integrating slang into formal and informal communication, whereas Gen Alpha faces challenges balancing slang usage with traditional literacy skills. The study also highlights the economic relevance of youth slang, as brands adopt generational language to engage audiences effectively. The study emphasizes the adaptive and expressive nature of youth slang, which serves as both a creative tool and a cultural identifier in the digital era. However, challenges such as maintaining traditional literacy skills and linguistic diversity warrant further attention. It is recommended that educators, policymakers, and marketers leverage these insights to bridge generational communication gaps, design effective learning strategies, and create relatable marketing campaigns. Future research should explore longitudinal studies and cross-cultural comparisons to deepen our understanding of the evolution and impact of youth language.